Increasing the energy efficiency of the impulse magnetizing process - Meyer, Alexander Wilhelm; Nolte, Christian; Fischer, Carina; Sauerhofer, Andreas; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Magnetizing rare earth magnets with high coercivity needs strong magnetic fields. To create the necessary field strength, copper coils are used requiring current strengths of several kA. Since the electrical resistance of copper differs from zero, this also means enormous thermal losses. Hence to reduce the losses and to avoid thermal damage of the coil, only short current pulses are applied generated by a pulse magnetizer. However, the efficiency of the process is very poor and lies in the lower per mil range [2]. The presented paper explains the impulse magnetization process in detail with focus on the losses within the magnetization device. Further different material parameters influencing the saturation field strength, such as conductivity, size and diameter to length ratio are presented and possibilities to improve the energy efficiency are shown.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric drive; magnetizer; permanent magnet; pulsed field magnetization; rotor assembly; synchronous mtor

Webbasierte Werkerinformationssysteme: Datenaufbereitung und -darstellung für die Werkerführung im Global Cross Enterprise Engineering - Fischer, Carina; Lušić, M.; Bönig, Jochen; Hornfeck, R.; Franke, Jörg (wt Werkstattstechnik - Online, 2014)
Globalization does not only affect enterprises in areas such as processing and transportation of material goods, but also with a view to the associated data flows. Distributed data generation and processing places higher demands on data fusion and local use. Especially product development data have to be made available for production planning and execution in a timely, efficient and targeted way. This paper presents an approach for use in manual assembly in the field of electromobility.
CRIS-Team Scopus Importer:2023-03-07